Outcome of Depressed Cranial Fracture: A single centre Experience of 490 Cases with short literature Review - Karki, Mohan; Roka, Yam Bahadur (Nepal Journal of Neuroscience, 2022)
Introduction: Depressed cranial fractures (DCFs) are one of the serious head injuries where road traffic accident (RTA) is the most common cause. So, we have assessed the outcome in surgically managed cases of depressed cranial fracture following head injury and study the factors which may affect the surgical outcome of patients. Materials and methods: A retrospective assessment of 490 consecutive cases was undertaken who went surgery for depressed cranial fracture (DCF) in Department of Neurosurgery, Neuro-Cardio and Multispecialty Hospital, Biratnagar, Nepal, from January 2011 to December 2021. All age groups (except< 1 year) were included in this study and diagnosis confirmed by CT scan of brain with bone window. Outcome was assessed by Glasgow outcome scale. Results: The incidence of depressed cranial fracture was highest in road traffic accident (RTA) and in the age group of 20-40 years. There was predominance of male over female with ratio 5.53:1. There was a significant correlation between age, mode of injury, fracture site, GCS at admission and intracranial bleed with outcome. Similarly, the complications such as CSF leakage, seizure were significant association with outcome. Of all 490 cases, most of them were operated within 5 hour with overall mortality rate of 0.40%. Conclusions: Our study concluded that patient who underwent surgery for DCFs, with GCS >13 at the time of admission, age <40 year and no hospital delay (<5hour) had better outcomes. Incidence of RTAs was noted comparatively higher rate in age 20-40 year, which can help us to find out best strategic management option.